Gastric microbiome of Indian patients with Helicobacter pylori infection, and their interaction networks. Issue 1 (December 2017) - Das, Anubhav; Pereira, Verima; Saxena, Shruti; Ghosh, Tarini; Anbumani, D.; Bag, Satyabrata; Das, Bhabatosh; Nair, G.; Abraham, Philip; Mande, Sharmila
Abstract The gastric microbiome is suspected to have a role in the causation of diseases byHelicobacter pylori . Reports on their relative abundance vis-à-visH. pylori are available from various ethnic and geographic groups, but little is known about their interaction patterns. Endoscopic mucosal biopsy samples from the gastric antrum and corpus of 39 patients with suspectedH. pylori infection were collected and microbiomes were analyzed by 16S rDNA profiling. Four groups of samples were identified, which harboredHelicobacter as well as a diverse group of bacteria includingLactobacillus, Halomonas andPrevotella . There was a negative association between the microbiome diversity andHelicobacter abundance. Network analyses showed thatHelicobacter had negative interactions with members of the gastric microbiome, while other microbes interacted positively with each other, showing a higher tendency towards intra-cluster co-occurrence/co-operation. Cross-geographic comparisons suggested the presence of region-specific microbial abundance profiles. We report the microbial diversity, abundance variation and interaction patterns of the gastric microbiota of Indian patients withH. pylori infection and present a comparison of the same with the gastric microbial ecology in samples from different geographic regions. Such microbial abundance profiles and microbial interactions can help in understanding the pathophysiology of gastric ailments and can thus help in development of new strategies to curb it.